An analysis into client based banking applications in South Africa - Naidoo, Drushen (My University, 2014)
The relationship between customers and their banks is becoming more dynamic (Ernst and Young, 2012). Customers are seeking greater control in their banking relationship. They are switching banks, changing their behaviours and seeking efficiencies. Banks need to reconfigure their business models, revaluate assumptions and fundamentally change how they interact with customers (Ernst and Young, 2012). It is estimated that there are over 10 million active smartphones in South Africa (Deloitte, 2013). The convergence of banking services and mobile technologies allows users to conduct banking service at any time or place through mobile banking (Gu, Lee, & Suh, 2009). The advent of smartphones and tablets has allowed banks to enhance the delivery of mobile financial services through the development of client based banking applications. These client based smartphone applications are developed for specific mobile operating systems such as Apple’s iOS, Google’s Android, Blackberry’s Blackberry OS7.1, 6.0 and 5.0. Smartphones will allow banks to leverage newer mobile technologies, harness analytics gathered through use of their applications to position products and services that will be of interest to their customers. This could result in increased revenues and it also provides an opportunity to increase market penetration. “ As banks develop their strategies for giving customers access to their accounts through cell phones and other mobile devices, they should also regard this emerging platform as a potential catalyst for generating operational efficiencies and as a vehicle for new revenue sources.“ (Deloitte Development, 2010) This research attempts to analyse and evaluate the usage patterns of clientbased mobile banking applications in South Africa by trying to ascertain what functionalities are performed on mobile banking applications and how often they are performed. This paper attempts to address these questions by building on (Trudel, Boeck, Bastonnais, Rabec, & Bergeron, 2011) typology of functionalities 5 performed on mobile banking applications by including a new construct, Frequency of Use in the determination of usage patterns
MBA thesis
Keywords: Banks and banking; Client-based banking; Mobile banking